2020
DOI: 10.3390/polym12020365
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Amplitude Oscillatory Shear Rheology of Model Branched Polystyrene (PS) Melts

Abstract: Linear and nonlinear rheological properties of model comb polystyrenes (PS) with loosely to densely grafted architectures were measured under small and medium amplitude oscillatory shear (SAOS and MAOS) flow. This comb PS set had the same length of backbone and branches but varied in the number of branches from 3 to 120 branches. Linear viscoelastic properties of the comb PS were compared with the hierarchical model predictions. The model underpredicted zero-shear viscosity and backbone plateau modulus of dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…In previous studies of our group, Abbasi and co-workers [18][19][20] used anionic polymerization to synthesize a series of monodisperse atactic LCB comb PS with the same backbone length (M w,bb = 290 kg mol −1 ) and similar, well-entangled branch length (M w,br = 44 kg mol −1 ≈ 3 M e ), but varying number of branches per backbone, N br , from 3 to 190. Those comb PS covered a wide range of conformational regimes from loosely grafted to densely grafted combs and loosely grafted bottlebrush conformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of our group, Abbasi and co-workers [18][19][20] used anionic polymerization to synthesize a series of monodisperse atactic LCB comb PS with the same backbone length (M w,bb = 290 kg mol −1 ) and similar, well-entangled branch length (M w,br = 44 kg mol −1 ≈ 3 M e ), but varying number of branches per backbone, N br , from 3 to 190. Those comb PS covered a wide range of conformational regimes from loosely grafted to densely grafted combs and loosely grafted bottlebrush conformations.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Furthermore, the dynamic tube dilution was expected to decrease the effective number of entanglements along the backbone. [18,19] Therefore, even though branching is known to have a positive impact on strain hardening, it was shown that, for the given model system above a certain number of side chains, the elongational performance in uniaxial extension as well as foam expansion is negatively affected. Consequently, excessive side chain crowding will not further increase the SHF.…”
Section: Introductionmentioning
confidence: 99%
“…29,31 Hydrogel formation is typically verified by inverted tube tests or small angle oscillatory shear rheology (SAOS); the latter technique probes the transition of material properties at the gelation point, which change from a primarily viscous to a primarily elastic response. 32 SAOS, tensile testing, and compression tests are also used to determine the mechanical properties, which are often compared to swelling and smallangle neutron scattering data to investigate the gel microstructure. 29,31 None of these techniques, however, provides information about specific chemical crosslinking within the material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Next, we investigated the nonlinear behavior of unentangled star PS under MAOS flow. Recently, the MAOS test has been utilized to characterize polymers with different topologies, such as linear, 3-arm star, comb, and bottlebrush structures. Herein, the MAOS test was utilized to distinguish between unentangled star PS and linear PS, because its results reflect the information on relaxation spectra in a complex manner. , Several material functions are available to describe the material response in a MAOS regime.…”
mentioning
confidence: 99%